Enhancement Optical Characterized of Tin Oxide in Polymer Polyvinyl alcohol Colloid Prepared by Laser Ablation Method (Baghdad Science Journal, 2024)
Nanocomposites are appropriate materials to meet emerging demands resulting from advances in science and technology. Components with novel structures and better efficiency compared to conventionally processed components are required for technological advances. In this research, polymer-inorganic colloidal nanocomposites can be created by using pulsed laser ablation for tin oxide nanoparticles in polyvinyl alcohol as a host. The optical characteristics and absorption spectra were used to look into the optical characteristics of the nanocomposite. The optical band gap (Eg) was measured; indirect transition values for pure polymer polyvinyl alcohol were determined to be 5 eV and 3.5 eV for PVA-SnO2 nanocomposite. The samples were measured for their extinction coefficient (k), refractive index (n), and dielectric constant. Nanocomposites' dielectric constant decreased while their absorption coefficient, refractive index, and extinction coefficient all increased. The nanocomposites have a high absorbency in the UV region and may be utilized for covering materials to radiation protecting applications. Write a brief abstract about your paper’s subject of study. Write a brief abstract about your paper’s subject of study. Write a brief abstract about your paper’s subject of study. Write a brief abstract about your paper’s subject of study. Write a brief abstract about your paper’s subject of study. Write a brief abstract about your paper’s subject of study.